Progress and challenges in drinking water access and poverty: A bibliomtric analysis (1995-2023) - Pisfil-Benites, Nilthon; Damian-sandoval, Luz Maria; Tuñoque-Morante, Luis; Vidal-Taboada, Silvia Lourdes (LACCEI, 2024)
In recent decades, there has been a growing interest in research on drinking water supply in low-income areas, with the aim of closing the knowledge gaps related to this issue, so this study focused on reviewing the progress made in research on access to drinking water and poverty. The method used to achieve this objective was bibliometric analysis, covering the period from 1995 to 2023. In addition, the Scopus database was used to collect 435 papers from 328 scientific journals. The results were further analysed using Bibliometrix and the viewer VOSviewer. Relevant research areas such as public health, risk factors, education and sustainable development were identified. It also highlighted cross-country collaboration, the most productive authors, and topics to be further explored in water, sanitation and health.